Proadi-SUS: analysis of financial resources in the three-year periods 2009-2011, 2012-2014 and 2015-2017 - Julia Amorim Santos; Luciana Palhares; Aquilas Mendes (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To characterize the tax exemption resources used in the Support Program for Institutional Development of the Unified Health System (Proadi-SUS) in the 3-year periods 2009-2011, 2012-2014, 2015-2017, considering the total volume of resources linked to the debate on tax expenditures on health and the constitution of a "new form of philanthropy" in the sector. METHODS To understand the philanthropic sector, tax expenditures between 2001 and 2017 were analyzed. To evaluate the resources used in the program, the values of projects and areas of activity were examined. RESULTS A real increase in the values of general tax expenses and tax expenses referring to the philanthropic sector was found. There was also a real increase in the program's resources. A total of 407 projects were carried out, amounting to R$ 3.4 billion for the period. An analysis of the average value of the projects shows an increase in values for all hospitals included in the program, with the exception of one of the institutions. In the 2009-2011 and 2012-2014 periods, the area with the highest number of projects and the most resources was "Management techniques and operation in health services". In the 3-year period 2015-2017, however, the sector that received the most investments and the largest number of projects developed was "Human Resources Training". CONCLUSION The program characterizes a different expression of the public-private partnership in the health sector linked to the principles of the new public management. As a development for future investigations, a qualitative characterization of the projects developed and the actions' impact on the public sector demands is necessary.